2011
DOI: 10.1007/s11270-011-0861-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Adsorption Isotherms of Bisphenol A, Estrone, 17β-Estradiol, and 17α-Ethinylestradiol in Tropical Sediment Samples

Abstract: The sorption of four endocrine disruptors, bisphenol A (BPA), estrone (E1), 17β-estradiol (E2), and 17α-ethinylestradiol (EE2) in tropical sediment samples was studied in batch mode under different conditions of pH, time, and sediment amount. Data obtained from sorption experiments using the endocrine disruptors (EDs) and sediments containing different amounts of organic matter showed that there was a greater interaction between the EDs and organic matter (OM) present in the sediment, particularly at lower pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…O sedimento apresentou maior potencial tóxico do que o observado em água. Contudo, esse maior potencial tóxico observado no sedimento não pode ser atribuído unicamente aos elevados teores de metais, pois o sedimento da Guarapiranga possui significativo potencial de sorção de disruptores endócrinos (Cunha et al 2011) que também podem causar efeitos adversos aos organismos. Além disso, altos teores de amônio, altamente tóxico à biota, podem ser encontrados em sedimentos com baixos teores de OD, como o registrado, devido ao processo de nitrificação ser pouco eficiente (Esteves 2011).…”
Section: Discussionunclassified
“…O sedimento apresentou maior potencial tóxico do que o observado em água. Contudo, esse maior potencial tóxico observado no sedimento não pode ser atribuído unicamente aos elevados teores de metais, pois o sedimento da Guarapiranga possui significativo potencial de sorção de disruptores endócrinos (Cunha et al 2011) que também podem causar efeitos adversos aos organismos. Além disso, altos teores de amônio, altamente tóxico à biota, podem ser encontrados em sedimentos com baixos teores de OD, como o registrado, devido ao processo de nitrificação ser pouco eficiente (Esteves 2011).…”
Section: Discussionunclassified
“…These compounds have been detected in several environmental compartments such as air, water, soil, sediment, and biota (Salgueiro-González et al, 2015;Nurulnadia et al, 2014;Jakimska et al, 2013;Maggioni et al, 2013;Bach et al, 2012). Due to the its higher water solubility when compared to AP and phthalates, and its relatively high log K ow value (Table 3) it may be predicted that BPA has a wide distribution in the aquatic environment Cunha et al, 2012). This hypothesis, however, needs to be further investigated.…”
Section: Alkylphenols and Bisphenol Amentioning
confidence: 99%
“…6b). It is widely recognized that the SOM is the principal factor controlling adsorption of organic compounds by sediments (Sun et al 2007;Cunha et al 2012). Cunha et al (2012) studied the adsorption of BPA, E2, EE2, and E1 onto two types of sediments and found that the K f values increased significantly from 1.7×10 −3 -3.1×10 −3 for S 1 to 4.2-7.4×10 −2 for S 2 due to …”
Section: Interaction Mechanisms Between Edcs and Sedimentsmentioning
confidence: 99%
“…Adsorption of EDCs and factors affecting their adsorption behaviors have been widely studied (e.g. Qiao et al 2008;Luo et al 2009;Cunha et al 2012;Kiran and Venkata 2012;Wang et al 2012). Dobor et al (2012) investigated the adsorption of selected acidic drugs by river sediments and found that the adsorption amount was positively correlated with the organic matter content (OM) and negatively correlated with pH.…”
Section: Introductionmentioning
confidence: 99%